Gender differences of the association between work-related stressors and mental health among Chinese medical professionals: a nationwide cross-sectional study - Chen, Lin; Wu, Lihong; Xia, Jingjing; Cai, Xixuan; Chen, Liying (Frontiers in Public Health, 2025)
BackgroundChinese medical professionals are under tremendous work pressure, which greatly undermines their mental health, hinders professional performance and impairs the quality of healthcare. However, the specific work-related stressor that affects mental health most and whether gender difference plays a role are not yet known. This study aims to investigate the association between work-related stressors and mental health among medical professionals in China.MethodsA cross-sectional online survey was conducted from September 29, 2022 to January 18, 2023 by recruiting 2,976 medical professionals from three representative provinces in China through purposive sampling. Anxiety and depressive symptoms were measured by the 7-item Generalized Anxiety Disorder (GAD-7) scale and Patient Health Questionnaire-9 (PHQ-9) scale. Logistic regression models were performed to identify work-related stressor significantly associated with mental health and stratified by gender.ResultsThe prevalence of major depressive and anxiety symptoms among Chinese medical professionals was 28.2% (839/2976) and 24.0% (714/2976), respectively. Among the subjects, 43.7% (1,302/2976) of subjects reported having ≥3 work-related stressors, which was positively related to both major depressive and anxiety symptoms. The following work-related stressors were positively associated with major depressive symptoms: violence against medical staff and promotion pressure among males; medical dispute among females. The following work-related stressors were positively associated with major anxiety symptoms: medical dispute and promotion pressure among males. While no work-related stressor showed significant association with major anxiety symptoms among females.ConclusionThese findings identified the specific work-related stressors related with the mental health, and gender differences are indicated in this relationship. Interventions directing at improving doctor-patient relationship may help to improve mental health of Chinese medical professionals. Reforming promotion system may mitigate the anxiety symptoms of male medical professionals.